2020
DOI: 10.1002/adma.201907623
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Repairing Tin‐Based Perovskite Solar Cells with a Breakthrough Efficiency Over 11%

Abstract: The development of tin (Sn)‐based perovskite solar cells (PSCs) is hindered by their lower power conversion efficiency and poorer stability compared to the lead‐based ones, which arise from the easy oxidation of Sn2+ to Sn4+. Herein, phenylhydrazine hydrochloride (PHCl) is introduced into FASnI3 (FA = NH2CH  NH2+) perovskite films to reduce the existing Sn4+ and prevent the further degradation of FASnI3, since PHCl has a reductive hydrazino group and a hydrophobic phenyl group. Consequently, the device achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
197
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(203 citation statements)
references
References 43 publications
5
197
1
Order By: Relevance
“…Note that the back-contact electrodes of these regular planar or mesoscopic devices were made by thermal evaporation of silver metal under high vacuum condition that is limited to their future industrial scalability. While the planar devices adopt ~200 nm thickness, closely associated with the effective charge diffusion length, for high-performance tin perovskites in solar cells, 14,15,27,28,[32][33][34]41 the 1 μm thick Al 2 O 3 insulating film in the mesoscopic devices is too harsh in terms of effective charge carrier diffusion for the tin perovskites. The further improvement in PCE is likely made by decreasing the Al 2 O 3 thickness.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the back-contact electrodes of these regular planar or mesoscopic devices were made by thermal evaporation of silver metal under high vacuum condition that is limited to their future industrial scalability. While the planar devices adopt ~200 nm thickness, closely associated with the effective charge diffusion length, for high-performance tin perovskites in solar cells, 14,15,27,28,[32][33][34]41 the 1 μm thick Al 2 O 3 insulating film in the mesoscopic devices is too harsh in terms of effective charge carrier diffusion for the tin perovskites. The further improvement in PCE is likely made by decreasing the Al 2 O 3 thickness.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…9 Such tin-based perovskites have been extended to other applications such as transistors, 10 photodetectors, 11 light-emitting diodes 12 and lasers. 13 For highperformance PSC, tin perovskites have evolved on suppressing oxidation of tin (from Sn 2+ to Sn 4+ ), pinholes and surface defects while improving crystallinity through an exploration of hybrid cations or anions, [14][15][16][17][18][19][20][21][22][23] additives [24][25][26][27][28][29][30][31][32][33] and interfacial engineering. [34][35][36][37] The additive approach is effective regardless of the type of tin perovskite and its interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant PSC showed an increased PCE up to 8.48%. [ 68 ] Recently, Huang et al [ 69 ] included phenylhydrazine hydrochloride (PHCl) in FASnI 3 films to passivate trap states and improve the stability of the respective PSCs. Time‐resolved photoluminescence (TRPL) and Mott–Schottky (M–S) analysis showed that the FASnI 3 film with 5.0% PHCl resulted in ≈3 times longer carrier lifetime and ≈3.5 times higher built‐in voltage than those of the control film without PHCl.…”
Section: The Influence Of Lewis Base Additives On Perovskite Solar Pementioning
confidence: 99%
“…S. Das et al, fabricated perovskite solar cell and obtained an average efficiency of 16.34% [15]. C. Wang et al, reported an efficiency of 11.4% from lead free PSC [16]. S. Abdelaziz et al, numerically modelled and calculated an efficiency of 14.03% from formamidinium tin based perovskite solar cell [17].…”
Section: Introductionmentioning
confidence: 99%